Indonesian Integral Law Based on Pancasila - Yogi Prasetyo (Pancasila and Law Review, 2022)
This study aims to explain the integral legal thinking which is constructed based on the values of Pancasila. In this study using a literature study research method with a philosophical approach. The data in the research such as; books, journals, articles and various scientific works are collected through library research. The data analysis technique used descriptive, hermeneutic and heuristic analysis. The results of the research show that it is important to make Pancasila an integral legal thinking in Indonesia, because of the strategic position of Pancasila in the life of the nation and legal issues that urgently need reform in accordance with the norms that live and develop in society as reflected in the values of Pancasila. Good law is law that is excavated from authentic sources, namely laws that apply in the real life of everyday people, not foreign laws that are imposed as a result of the colonial legacy. The integral legal thinking of Pancasila is a way of thinking, acting and acting legally based on the values of divinity, humanity, Indonesian unity, deliberation and social justice for all Indonesian people.